The Effect of Service Quality on Customer Satisfaction in the Front Office Department During COVID-19 - Subakti, Agung Gita; Maribelle, Maria Gracia; Sanjaya, Wellyansyah (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2023)
Purpose of the study: The COVID-19 pandemic has made the hotel continue improving its service quality to survive until the pandemic is over. This study aims to understand how the variable service quality of front office employees during COVID-19 on customer satisfaction. Design/methodology: The design of this study used an online survey. Purposive sampling of hotel guests staying at JW Marriott Hotel Jakarta was conducted from January 2022 to May. Data analysis was done using IBM SPSS 25 software. Findings: This study's findings show an influence between service quality variables and consumer satisfaction variables during COVID-19 in the front office department of JW Marriott Hotel Jakarta. Research limitations/Implications: In this study, there is only one independent variable, so it is not complete to explain what factors affect consumer satisfaction (dependent). In the following study, free variables (independent) will be added to provide even better advice to the company and as a learning for researchers and readers. Novelty/Originality of the study: This research focuses on the quality of services carried out in the hotel’s front office department during the COVID-19 pandemic.